Can Non-steroidal Anti-inflammatory Drugs Affect the Interaction Between Receptor Binding Domain of SARS-COV-2 Spike and the Human ACE2 Receptor? A Computational Biophysical Study - González-Paz, Lenin A.; Lossada, Carla A.; Fernández-Materán, Francelys V.; Paz, J. L.; Vera-Villalobos, Joan; Alvarado, Ysaias J. (Frontiers in Physics, 2020)
SARS-CoV-2 has caused millions of infections and more than 600,000 deaths worldwide. Despite the wide number of studies to date, there is no specifically effective treatment available for SARS-CoV-2. However, it has been proposed to target reused drugs with potential antiviral activity to the interfere between the angiotensin-converting enzyme 2 (ACE2) and the receptor binding domain (RBD) interface of SARS-CoV-2 to avoid cell recognition. Several non-steroidal anti-inflammatory drugs (NSAIDs) have been reported to have some type of activity against a wide variety of viruses including SARS-CoV-2. Therefore, we carried out an exhaustive computational biophysical study of various NSAIDs targeting the RBD-ACE2 complex using multiple comparative analysis of docking and molecular dynamics. Only the Ibuprofen (Propionic acid derivative), Aspirin (Salicylate), and the Acetaminophen (p-aminophenol derivative) had a thermodynamically favorable docking with the complex RBD-ACE2 interface under the conditions of this study. Although, Ibuprofen was the NSAIDs most thermodynamically favorable docking in the shortest simulation time, and was the major inducer of structural changes, conformational changes, and overall changes in the complex throughout the simulation, including disturbances in composition and distribution of cavities at the interface. Results that point to ibuprofen as an NSAID that, under the conditions outlined in this investigation, may have the highest probability of generating a disturbance in the stability of the RBD-ACE2 complex. This statement, although it could contribute information for the empirical treatment and prevention of COVID-19, represents only a theoretical orientation and approach, and requires its experimental demonstration because our predictions cannot secure a pharmacologically and clinically relevant interaction. Therefore, our results suggest a possible alternative mechanism of action of some NSAIDs against COVID-19 which is relevant because there are no reports related to this, in addition to their well-known anti-inflammatory properties.